Movimento Afro-brasileiro Pró-Libertação de Angola (MABLA): "um amplo movimento" - relação Brasil e Angola de 1960 a 1975 - Santos, José Francisco dos (2010)
The research records the relationship between Brazil and Angola, between the period of 1960 and 1970, analyzing the Afro-Brazilian Movement Pro- Liberation of Angola (MABLA); a movement that involves various sectors of the society in Sao Paulo and Rio de Janeiro. The aim of this movement was to create awareness to the Brazilian public about the problems faced by the Portuguese colonies in Africa; this research focused especially on the actions leading on to the independence of Angola. There were many burdens because Angola s independence happened in the middle of the Cold War, and an aggravating factor was the Salazar s regime which was established in Portugal in 1926 and was very anachronistic. This regime had close links to Brazil almost till the end, in 1974, with the Carnation Revolution. MABLA had established relationship with the Popular Movement for Angola s Liberation (MPLA), a movement which had closed ties to the Soviet Union and Cuba. In the coup d´état of April 1, 1964, the Civil-Military regime aligned with the United States, some militants of MABL were arrested. This same Civil-Military regime was the first to recognize Angola s independence on November 11, 1975, led by MPLA. Therefore, the research examines the development of relationships between two countries, trying to understand the contexts of the decade 1960 to 1970 regarding its transformations